Gender, crop diversification, and nutrition in irrigation catchment areas in the central dry zones in Myanmar: Implications for agricultural development support - Ragasa, Catherine; Mahrt, Kristi; Aung, Zin Wai; Lambrecht, Isabel B.; Scott, Jessica (International Food Policy Research Institute, 2020)
This report describes the baseline data collected from 1,835 men and women respondents in 998 households in two irrigation sites in the central dry zone in Myanmar to help diagnose, design, and test interventions to enhance the Myanmar Agricultural Development Support Project’s impacts on gender equality and nutrition. Baseline data show large gender gaps, in which fewer women than men achieved adequacy in all 11 indicators of empowerment. Eighty-nine percent of women versus 64 percent of men respondents were not empowered, and 66 percent of dual-adult households have gender gaps. The main contributors of disempowerment among women were high tolerance and acceptance of intimate partner violence, lack of work balance, and low membership in groups, especially influential groups. Although 95 percent of respondents owned smartphones, women were less likely than men to access Internet or social media through their phones. Thirty-nine percent of respondents received rice-related information and half received health-related information. Nine to 14 percent of respondents attended agriculture- or health-related training courses. Women were significantly less likely to receive agriculture and nutrition-related information and training than men. The dietary diversity score, a common indicator of diet quality and a good proxy for nutrition, is low in the sample. The individual dietary diversity score was 4.32, with no significant difference between women and men and no major differences between irrigation water users and other households. Dairy, nuts and seeds, eggs, vitamin-A-rich fruits and vegetables, and other fruits are not commonly or frequently consumed by a majority of respondents. Beans and dark leafy vegetables, which are relatively abundant in the study context, are consumed by only 38–48 percent of the respondents on a daily basis. Nutrition education highlighting dietary diversity can help the sample communities achieve better nutrition. Overall, most women and men in the sample communities employ good sanitation practices, but more people need to be sensitized on proper garbage disposal, drinking water treatment, and proper and more frequent handwashing.